Hypocrisy in Professors’ Performance and its Correlation to Students’ Attitudes towards their Professors - Yousif, Ali Jerad (International Journal of Psychosocial Rehabilitation, 2020)
This study looks into hypocrisy in the academic performance of professors, how it is perceived by postgraduate students and how it impacts their attitudes towards their professors. Accordingly the variables of gender (male-female) and major (medicine-engineering-agriculture-pure sciences-and social or human sciences) were selected. The two scales were set up according to the essential academic steps, and the use of appropriate statistical methods. The study concluded that there is a certain percentage of hypocrisy in the professors’ academic performance, positive trends towards professors, there is a significant statistical difference in the major variable, no difference for the gender variable, and there is a positive correlation between the two variables). Finally, the study presented recommendations and suggestions.